2021
DOI: 10.3390/jcm10163470
|View full text |Cite
|
Sign up to set email alerts
|

Does Posterior Cruciate Ligament Retention or Sacrifice in Total Knee Replacement Affect Proprioception? A Systematic Review

Abstract: Background: Proprioception is an important part of the somatosensory system involved in human motion control, which is fundamental for activities of daily living, exercise, and sport-specific gestures. When total knee arthroplasty (TKA) is performed, the posterior cruciate ligament (PCL) can be retained, replaced, or discarded. The PCL seems to be responsible for maintaining the integrity of the joint position sense (JPS) and joint kinesthesia. The aim of this review was to assess the effect of PCL on knee joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Several studies have compared patients’ outcomes with PCL-preserved or sacrificed TKA; generally, no significant differences were described between the two groups of patients [ 34 , 43 , 44 , 45 ]. Thippanne et al [ 43 ] reported no statistically significant differences for FJS between 169 PCL-retained TKAs and 178 PCL-sacrificed TKAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have compared patients’ outcomes with PCL-preserved or sacrificed TKA; generally, no significant differences were described between the two groups of patients [ 34 , 43 , 44 , 45 ]. Thippanne et al [ 43 ] reported no statistically significant differences for FJS between 169 PCL-retained TKAs and 178 PCL-sacrificed TKAs.…”
Section: Discussionmentioning
confidence: 99%
“…Until August 2019, the PCL was always sacrificed in all treated patients. Starting in September 2019, considering the theoretical advantages of PCL preservation based on recent scientific evidence [ 34 , 35 , 36 , 37 ], such as increased anteroposterior stability and improved proprioception, we decided to retain the PCL in every case. In patients with tight flexion, space was evident after bone resections and gap balancing based on tibial recut was performed ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, they did not analyze in detail the number of mechanoreceptors of the PCL in patients with different degrees of OA, and they did not know whether the value of retaining PCLs in patients with OA at all levels was the same. The clinical results of Vandekerckhove et al, 22 Götz et al, 12 and Bravi et al 3 show that preservation of PCLs cannot significantly improve the proprioception or postural stability of the joint after TKA. Nevertheless, their study did not indicate the degree of OA in the experimental group and the control group, which does not reflect the true preservation value of the PCL.…”
Section: Discussionmentioning
confidence: 99%
“…2 Proprioception includes perception of the static position, displacement, velocity, acceleration, and muscle force of body parts. 3 Proprioception depends on mechanoreceptors, which are distributed in many tissues of the knee joint. C xabuk et al 5 found that there are mechanoreceptors at the PCL, the anterior articular capsule, and the medial meniscus, which attaches to the articular capsule.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main issues in total knee arthroplasty is the retention or the sacrifice of PCL, as it seems to affect the proprioception of the knee. Bravi et al concluded that the retention of the PCL does not substantially improve the joint proprioception after TKR [ 39 ].…”
Section: Discussionmentioning
confidence: 99%